A liberdade de cátedra e o lugar da burocracia de Estado: um estudo sobre a disputa por sentidos de justiça e a censura nas ações dos operadores do direito brasileiro - Machado, Naara Maia Araújo do Rêgo (2021)
After the outbreak of debates on the degree of political and ideological instillation in Brazilian schools, driven by the movement Escola sem Partido originated in 2004, we faced the emergence of plenty of social groups’ actions and the powerful decisions of State agents that endangered the freedom of professorship. Furthermore, in recent years, conservative forces have gained ground in the legislative power, proposing numerous bills to limit didactic pedagogical freedom in schools. Following the implications that were raised by the debate, there was a wave of denunciations and accusations of ideologizing practices within the classroom, calling into question the role of education and educators in the moral and intellectual formation of the individual. This issue, however, raises other angles of analysis within the bureaucratic apparatus of the State regarding the reasons and moral values covered by the actors of power who act in its name. In this sense, choosing documentary research as a method, it started from a sample of documents collected in some Brazilian states, journalistic news and scientific works narrating experiences in which the issue of academic freedom was problematic. Evaluation and correlation were made of the speeches and high values by the authorities of the Brazilian Justice that were mobilized for the demand of the support groups to the teaching censorship, endorsing the senses of justice of these groups in dispute with the freedoms defended by the educators. Then, from the speeches, it was concluded that ideas such as “freedom” and “constitutionality” take on different meanings in the spaces where they are mobilized. The study used the theoretical support of the work of Pierre Bourdieu and Zygmunt Bauman about the bureaucracy and of its inflections during Modernity, realizing how critical moments in history that have inquired morality in human actions launched a major critique on how the bureaucratic ethos of the State reverberates in social life.